Centered Educational Philanthropy from the Perspective of the Qur'an: Almsgiving as a Continuous Charity - Indarwati Indarwati; Imam Machali; Najmee Bindulem (ZAD Al-Mufassirin, 2026)
Educational philanthropy is a form of social empathy that plays a crucial role in assisting financially challenged communities in accessing education. Ongoing economic inequality impacts the educational sustainability of students, making philanthropy a social mechanism for strengthening solidarity and expanding learning opportunities. This study aims to analyze the role of philanthropic funds in supporting educational access and sustainability. The methodology used is a qualitative approach through literature studies and conceptual analysis of philanthropic values ​​from an Islamic perspective derived from the Qur'an. The results show that financial barriers can be overcome through philanthropic practices such as providing scholarships, educational assistance, and social support based on religious values. Educational philanthropy has not only a socio-economic dimension but also a theological one as the implementation of Qur'anic values ​​in social life. The novelty of this study lies in the emphasis on students as the primary recipients of philanthropy and the integration of Qur'anic values ​​as the basis for social ethics. The implication is that strengthening philanthropy based on religious values ​​can support a more inclusive and equitable education system.